2020
DOI: 10.1101/2020.01.28.922930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of acute physical exercise on motor sequence memory

Abstract: ABSTRACTAcute physical exercise improves memory functions by increasing neural plasticity in the hippocampus. In animals, a single session of physical exercise has been shown to boost anandamide (AEA), an endocannabinoid known to promote hippocampal plasticity. Hippocampal neuronal networks encode episodic memory representations, including the temporal organization of elements, and can thus benefit motor sequence learning. While previous work established that acute physical exe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
(42 reference statements)
2
5
0
Order By: Relevance
“…The number of participants may also explain why our signi cant associations did not survive multiple comparison corrections and the lack of mediation effects. However, our sample size is similar to other studies investigating vo2max in relationship to brain and cognitive variables (Manning et al 2022;Nilsson et al 2020;Bosch et al 2020), and also matched the size of other relevant studies whose used the same methodology than ours (Olivo et al 2021;Petkus et al 2021). Furthermore, we have also enhanced the validity of our design by performing thorough control analyses, contrasting 9 different hypotheses to the main hypothesis, and systematically covarying for relevant confounding factors such as age, gender, education, total intracranial volume, and max heart rate.…”
Section: Limitationssupporting
confidence: 62%
“…The number of participants may also explain why our signi cant associations did not survive multiple comparison corrections and the lack of mediation effects. However, our sample size is similar to other studies investigating vo2max in relationship to brain and cognitive variables (Manning et al 2022;Nilsson et al 2020;Bosch et al 2020), and also matched the size of other relevant studies whose used the same methodology than ours (Olivo et al 2021;Petkus et al 2021). Furthermore, we have also enhanced the validity of our design by performing thorough control analyses, contrasting 9 different hypotheses to the main hypothesis, and systematically covarying for relevant confounding factors such as age, gender, education, total intracranial volume, and max heart rate.…”
Section: Limitationssupporting
confidence: 62%
“…at is, the signal error can be adjusted according to the two input directions from the actual input signal direction to the actual expected signal output, respectively, to calculate the signal output, from the direction of the real expected signal output and then to the real expected input direction of the two directions, respectively, to calculate the signal error to adjust the signal error weight range and error threshold. In the study of the propagation method after the forward superposition of the signal, the input node signal is mainly the node on the actual output of the signal after the inverse superposition through the role of the hidden layer, and the actual output node signal can be generated through the non-linear transformation process [21]. If we find that the actual signal output node position does not coincide with the actual output node direction position of the actual input node expectation signal, the process of backward feedback propagation method for signal error compensation will be easily generated.…”
Section: Main Evaluation Methodmentioning
confidence: 99%
“…Most notably, the current study utilised a higher intensity exercise protocol, with participants reaching up to 90% of their estimated maximum heart rate during highintensity epochs, resulting in greater power output and overall exertion compared to Greeley and colleagues 41 . Although high-intensity exercise may impact motor skill acquisition, there appears to be a dose-response relationship in favour of higher-intensity exercise in supporting motor consolidation 32,33 . This may relate to the cascade of neurochemical changes induced by high-intensity exercise, which may maintain an interval environment favourable for memory consolidation, including increased circulation of catecholamines 82 , lactate 83 , and brain-derived neurotrophic factor (BDNF) 84 .…”
Section: Exercise and O Ine Learningmentioning
confidence: 97%
“…While some studies show that a single bout of acute cardiorespiratory exercise can improve motor performance and online learning [21][22][23] accumulating evidence indicates that exercise is particularly bene cial in enhancing the o ine consolidation of a new motor skill [24][25][26][27] . Although several studies have found no apparent bene t of acute exercise on motor consolidation [28][29][30][31] , a recent meta-analysis suggests this may be explained by variations in motor learning task and exercise characteristics Exercise intensity appears to be of particular importance, with greater bene ts following high-intensity exercise 32,33 . In addition to healthy young adults, there is emerging evidence that exercise can improve motor learning in clinical populations such as Parkinson's disease 34 , Huntington's disease 35 , or following a stroke 36 , however research into the bene ts of acute exercise for motor learning in healthy older adults is limited.…”
Section: Introductionmentioning
confidence: 99%